(untitled) (Journal of Bangladesh Institute of Planners, 2016)
The population growth and urbanization of Rajshahi metropolitan city shows an increasing trend. This paper attempts to figure out the influence of land use change on land price in Rajshahi city.As resources are limited, land resource is also limited to fulfill the demand for industrial, commercial, residential, and institutional uses of land. Land price varies with different types of land uses. The increasing demand for land is responsible for the increasing land price. To find out the effects of land use change on land price, a field survey was conducted within five selected wards in Rajshahi metropolitan area. Primary data is gathered from the field survey and required secondary data from master plan of Rajshahi prepared in 1984 and 2004. GIS software isused for generating maps and Microsoft Excel is used for analyzing the increasing trend of land price with the land use. The study has found out a correlation between the two factors that land price increases with the land use change. JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 17-26